Influência da suplementação da ração com diferentes doses de vitamina D sobre a proteína de interação com a tiorredoxina (TXNIP) no coração e suas vias de sinalização - Santos, Priscila Portugal dos [UNESP] (2015)
Vitamin D (VitD) deficiency has increased in recent years, becoming a public health problem. Additionally, VitD deficiency is associated with increased risk of chronic diseases developing, including cardiovascular diseases. These factors have encouraged the widespread use of this vitamin, without knowing well the alterations of different supplementation doses. Studies have shown that VitD is important for the cardiac development and function, however this vitamin can presented adverse cardiovascular effects, even at non-toxic doses. VitD acts in the target cells by binding to VitD receptor (VDR). Additionally, the thioredoxin-interacting protein (TXNIP) was identified and it expression is up-regulated by VitD. This protein acts in the regulation of signaling pathways (redox balance, apoptosis, inflammation, cell growth, metabolism energy) which can participate of the cardiac remodeling process. The aim of this study was to evaluate whether excess VitD supplementation, but in nontoxic doses, in the chow for 2 months results in change of TXNIP expression, cardiac remodeling with oxidative stress, apoptosis and alterations of inflammatory mediators and energy metabolism and whether, the supplementation increased time (for 4 months) leads to changes in cardiac structure and function. Experiment 1: 64 male rats was used and was divided into 3 groups - control (C, n = 21) received standard chow; VD3 (n = 22) and VD10 (n = 21) received 3,000 and 10,000 IU of cholecalciferol / kg of chow respectively, for 2 months; and Experiment 2: 46 male rats was used and was divided into 3 groups - control (C-4, n = 14) received standard chow; VD3-4 (n = 16) and VD10-4 (n = 14) received 3,000 and 10,000 IU of cholecalciferol / kg of chow respectively, for 4 months. After 2 and 4 months was performed echocardiography and after the animals were euthanized. The serum and the left ventricle of experiment 1 animals were used for biochemical analyzes. Statistical ...